2018
DOI: 10.1016/j.neuron.2018.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Two Forms of Synaptic Depression Produced by Differential Neuromodulation of Presynaptic Calcium Channels

Abstract: Neuromodulators are important regulators of synaptic transmission throughout the brain. At the presynaptic terminal, neuromodulation of calcium channels (CaVs) can affect transmission not only by changing neurotransmitter release probability, but also by shaping short-term plasticity (STP). Indeed, changes in STP are often considered a requirement for defining a presynaptic site of action. Nevertheless, some synapses exhibit non-canonical forms of neuromodulation, where release probability is altered without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 95 publications
2
53
1
Order By: Relevance
“…The similar effects of D1 receptor activation that we observed support the idea that the majority of commissural fibers is targeting layer V. Furthermore, Anastasiades et al () have also reported that D1 receptor activation enhances cortico‐cortical connectivity, supporting the results reported here. Contrary to results reported here, others have shown that D1 receptor activation suppresses commissural fiber‐evoked EPSCs in layer V pyramidal cells through a presynaptic mechanism involving modulation of calcium channels (Burke et al, ). However, these studies were conducted without the presence of GABA blockers, thus likely involving D1 modulatory effects on GABAergic interneurons.…”
Section: Discussioncontrasting
confidence: 99%
“…The similar effects of D1 receptor activation that we observed support the idea that the majority of commissural fibers is targeting layer V. Furthermore, Anastasiades et al () have also reported that D1 receptor activation enhances cortico‐cortical connectivity, supporting the results reported here. Contrary to results reported here, others have shown that D1 receptor activation suppresses commissural fiber‐evoked EPSCs in layer V pyramidal cells through a presynaptic mechanism involving modulation of calcium channels (Burke et al, ). However, these studies were conducted without the presence of GABA blockers, thus likely involving D1 modulatory effects on GABAergic interneurons.…”
Section: Discussioncontrasting
confidence: 99%
“… 57 Calcium dynamics in the presynaptic terminals are also influenced by neuromodulators such as adenosine 55 and dopamine. 58 …”
Section: Axonal Calcium Signals: As a Proxy For Presynaptic Activitymentioning
confidence: 99%
“…; Burke et al . ), the vast majority of studies use concentrations of calcium in the extracellular solution that are higher than physiological levels, between 2 and 4 mM, to support synaptic transmission and suppress intrinsic excitability. In this study, we determine the concentration of ionized calcium in human cerebrospinal fluid (hCSF), and characterize the effects of using physiological (~1.2 mM), as compared to standard (2 mM), artificial cerebrospinal fluid (aCSF) calcium on intrinsic neuronal excitability, synaptic transmission, paired‐pulse plasticity, and long‐term potentiation in rat CA1 pyramidal cells.…”
mentioning
confidence: 99%